PENGETAHUAN PERAWAT TENTANG FASE PENYEMBUHAN FRAKTUR POST OPEN REDUCATION INTERNAL FIXATION (ORIF) DI RUANG RAUDHAH 6 DAN 7 RSUDDR.ZAINOEL ABIDIN BANDA ACEH - Mohammad Hendro Mustaqim; Fakhrul Rizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The purpose of health development is the achieved healthy life ability for every citizen to establish the optimal health quality. The nurses care is beneficial for every individual to fulfill the biological, psychological, social, and spiritual needs. as in Indonesia, fractures often occur. Fractureis the condition where there is continuity cut off of bone structures. The bone fracture can be cured through a complex bone recovery. However, complication can be occurred either because of the traumatic effect or the recovery process. Bone fractures can be cured in conservative ways either by gips or by using internal or external fixation. The fractures itself occur due to the continuity cut off of bone tissue which is generally happened because of pressure or force. The aim of this research is to examine the nurses understanding about fracture recovery phases of open reduction internal fixation (ORIF) fracture post at Raudhah room 6 and 7 in dr. ZainoelAbidin Banda Aceh Hospital in 2018. The type of the research used is descriptive-explorative. The data collection is conducted by questionnaire. The research was conducted from May 30, 2018, to June 10, 2018. The samples of this study are all nurses incharge in the Raudhah room 6 and 7 with the total of 50 respondents through total sampling. The result of this study shows that nurse understanding about the inflammation phase is at good category with a total of 29 respondents (58%), As for the nurses understanding about the proliferation phase is at good category with a total of 30 respondents (60%). Nurses understanding about ossification phase is at good category with the total of 28 respondents (56%). The nurses understanding about the remodeling phase is at good category with the total of 31 respondents (62%). Therefore, it is expected that the nurses to improve their understanding of the post-fracture recovery of open reduction internal fixation.Keywords: nurses understanding on recovery phase of orif fracture